Синтез новых олигомеров на основе бетулина и некоторых дикарбоновых кислот - Яновский В. А.; Нечаева Е. А.; Бакибаев А. А. Абдигали Абдиманапович; Жук В. В.; Фитерер Е. П. Елена Петровна (2009, 2009)
В фонде НТБ ТПУ отсутствует